SEMANTIC AND LEXICAL PARADIGMATIC RELATIONS - Razaqova Sevinch; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article is devoted to the study of various linguistic points of view on paradigmatic relations, especially semantic and lexical paradigmatic relations, their essential features. A number of definitions are given and compared. In addition, the general and special features of semantic and lexical-paradigmatic relations, a deep look at the concept of relations, which were proposed by outstanding linguists, are given. The results of this article can help readers form a general linguistic understanding of paradigmatic relations.